2015
DOI: 10.2323/jgam.61.1
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid production by newly isolated red yeast <i>Rhodosporidium paludigenum</i>

Abstract: Indole 3-acetic acid (IAA) is the principal hormone which regulates various developmental and physiological processes in plants. IAA production is considered as a key trait for supporting plant growth. Hence, in this study, production of indole-3-acetic acid (IAA) by a basidiomycetous red yeast Rhodosporidium paludigenum DMKU-RP301 (AB920314) was investigated and improved by the optimization of the culture medium and culture conditions using one factor at a time (OFAT) and response surface methodology (RSM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 31 publications
6
30
0
Order By: Relevance
“…Some concerns exist that this concentration does not reflect all actual concentrations found in the wild or those produced by microbes. Many studies have shown that the amount of IAA that many bacteria and fungi can secrete was similar to or even more than 500 µM which is the highest dose we used here (Mohite, 2013;Limtong et al, 2014;Nutaratat et al, 2015;Nutaratat, Monprasit & Srisuk, 2017). According to our previous study, some fungi (e.g., Aureobasidium pullulans) can even can secrete more than 200 µg/mL IAA (∼1,000 µM) (Fu et al, 2016).…”
Section: Notesmentioning
confidence: 84%
“…Some concerns exist that this concentration does not reflect all actual concentrations found in the wild or those produced by microbes. Many studies have shown that the amount of IAA that many bacteria and fungi can secrete was similar to or even more than 500 µM which is the highest dose we used here (Mohite, 2013;Limtong et al, 2014;Nutaratat et al, 2015;Nutaratat, Monprasit & Srisuk, 2017). According to our previous study, some fungi (e.g., Aureobasidium pullulans) can even can secrete more than 200 µg/mL IAA (∼1,000 µM) (Fu et al, 2016).…”
Section: Notesmentioning
confidence: 84%
“…4, a high level of IAA (490 mg/L) was obtained when mannitol was added as the carbon source. Many researchers reported that carbon sources addition in culture medium increased IAA synthesis (Datta and Basu 2000; Nutaratat et al 2015).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, yeasts isolated from various natural habitats have been found to havepotential as effective producers of various biotechnological products worldwide. Various wild yeast species have been reported to have a vital role in modern industrial biotechnology, for example, for the production of citric acid [51], single cell proteins [52,53], ethanol [54,55], microbial oils [56][57][58], indole-3-acetic acid (IAA) [59], itaconic acid [60], glycolipid biosurfactants [49], arabitol [61], xylitol [62], erythritol and mannitol [63]. In this study, we isolated 217 yeast strains of 10 species in the Ascomycota and 35 species in the Basidiomycota.…”
Section: Discussionmentioning
confidence: 99%
“…Papiliotrema flavescens has been reported to be able to produce αgalactosidase [65]. The strains of R. paludigena and H. sinensis also showed the ability to produce large qualities of indole-3-acetic acid (IAA) [59]. D. churashimaensis and M. antarcticus, which previously belonged to the genus Pseudozyma, have been applied for itaconic acid production [60].…”
Section: Discussionmentioning
confidence: 99%